Detection of Anthelmintic Resistance in Sheep in and around Hassan district, Karnataka by Faecal Egg Count Reduction Test - Veena, M.; Puttalakshmamma, G. C.; Dhanalakshmi, H.; Naveenkumar, G. S. (International Journal of Livestock Research, 2020)
Anthelmintic resistance against commonly used anthelmintics, like fenbendazole and ivermectin was studied in sheep that are naturally infected with gastrointestinal nematodes in Hassan district, Karnataka by using faecal egg count reduction test (FECRT). Overall, 45 sheep farms were selected in the study out of which 26 farms were treated with fenbendazole and 19 farms were treated with ivermectin. The results of the present study revealed high level of resistance in 15 fenbendazole treated farms with mean FECR per cent ranging from 77 to 94 per cent, whereas among the 19 ivermectin treated farms 2 farms revealed resistance with mean FECR per cent ranging from 90 to 92 per cent. Further morphological characterization of the infective larvae derived from pre- and post- treatment faecal cultures was done. The post- treatment faecal cultures of fenbendazole treated farms revealed Haemonchus contortus as the predominant species in 12 farms and Trichostrongylus spp. in 3 farms. In ivermectin treated farms, H. contortus was predominant.